Strategies of Micro, Small, and Medium Enterprises in Traditional Culinary Innovation in the 4.0 Era: Strategi Usaha Mikro Kecil Menengah dalam Inovasi Kuliner Tradisional di era 4.0 - Zuriana, Khalida Zia; Rizky, M. Chaerul; Nabila, Salsa; Ginting, Sherly Anesha Br.; Arief, Yusril Bachtiar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The transition to Industry 4.0 demands strategic adaptation among micro, small, and medium enterprises (MSMEs) in the traditional food sector. Specific Background: Modern angkringan concepts like Café Kopkar represent an innovative response to this digital shift. Knowledge Gap: Despite emerging trends, there is limited empirical evidence on how digital-era strategies affect traditional culinary innovation in MSMEs. Aims: This study investigates the impact of Industry 4.0-oriented survival strategies on traditional culinary innovation in modern angkringan MSMEs. Results: Using regression analysis on data from 25 purposively selected owners and employees, findings reveal a significant positive effect of strategic adaptation—including technology use, consumer insight, and innovation—on culinary innovation. Novelty: The research highlights the pivotal role of Generation Z entrepreneurs in fusing modernity with local wisdom, maintaining cultural identity while leveraging social media and personalized service. Implications: These insights offer practical guidance for MSMEs in designing sustainable innovation strategies that preserve cultural heritage while remaining competitive in the digital age. Highlights: Highlights the role of digital strategies in preserving traditional culinary identity. Emphasizes Gen Z's potential in cultural entrepreneurship. Demonstrates how tech adaptation drives culinary innovation in MSMEs. Keywords : MSME Strategy, Culinary Innovation, Modern Angkringan, Industry 4.0, Local Wisdom